Disaster Policy, Participation, and Horizontal Conflict: Case Study Reconstruction Aid Funds of The Bantul Earthquake: Case Study Reconstruction Aid Funds of The Bantul Earthquake - Isnadi, Yuli; Asmarawati Handoyo (Jurnal Administrasi Publik (Public Administration Journal), 2023)
This investigation aims to show that the government’s policy without participation approach causes horizontal conflict in society. The case study is financial aid in reconstruction process for the earthquake’s victims in Bantul Regency, 2006-2007. This research collects secondary data, such as government’s documents, journals, books, news, and other relevant sources. Based on data analysis, we find that the absence of participation in policy making causes policy cannot accommodate the social context of the target group. As impact, community leaders and community members face a problematics situation that creates many problems during implementation. These problems, finally, lead the society into horizontal conflict. This finding might contribute in public policy and disaster management discourse, theoretical and practical, and build a path for the future research.